The Effects of Nordic Walking with Poles with an Integrated Resistance Shock Absorber on Red Blood Cell Distribution and Cardiorespiratory Efficiency in Postmenopausal Women—A Randomized Controlled Trial - Katarzyna Sobczak; Paweł Nowinka; Krystian Wochna; Katarzyna Domaszewska (Biology, 2023)
Background: Age-related reduction in exercise capacity is manifested by a rapid development of fatigue. Research confirmed the adverse prognostic value of red blood cell distribution width (RDW-CV), an independent factor in heart failure, coronary heart disease and myocardial infarction. Physical exercise improves and helps to maintain cardiorespiratory fitness. The aim of our study was to examine the impact of 8 weeks’ Nordic walking training with classic poles (NW) and NW training with poles with an integrated resistance shock absorber (NW with RSA) on RDW-CV levels and to assess correlations between RDW-CV levels and cardiorespiratory performance in postmenopausal women. Methods: In this study, 32 postmenopausal women (NW-16, NW with RSA-16) participated in eight weeks of walking training. The mean age of women was 66.56 ± 4.23 year. and BMI 26.99 ± 3.86 kg/m2. At the beginning and at the end of the study, spirometry and exercise tests were performed. Haematological parameters were determined in the venous blood. Results: Statistical analysis of differences in post-training changes in the parameters between the groups studied showed a significant difference in change in body weight (∆body weight) (p < 0.05; ES: 0.778), BMI (∆BMI) (p < 0.05; ES: 0.778), waist circumference (∆WC) (p < 0.05; ES: 1.225) and (∆RDW-SD) (p < 0.05; ES: 1.215). There were no changes in electrocardiographic and spirometric parameters. Conclusions: Based on the findings from the present study, it can be assumed that endurance and resistance exercise can significantly reduce disease severity and mortality. A clinical analysis of RDW levels, together with other cardiological and biochemical parameters, can provide practical prognostic information relating to cardiovascular disease, mortality risk and treatment outcomes.